PERAN MANAJEMEN KEUANGAN DAN DIGITAL MARKETING DALAM UPAYA MENINGKATKAN OMSET PENJUALAN KAOS PRIA BAGI UMKM TWOHERSHOP DI KOTA MEDAN - Bayu Prabowo; Muhammad Nasir; Yusril Mahendra; Zainarti Zainarti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
The role of financial management and digital marketing cannot be separated from the efforts of related stakeholders to realize growth while increasing prosperity while increasing sales revenue. One indicator of increasing the welfare of business actors is an increase in sales turnover. It is hoped that this condition can be achieved by maximizing digital marketing strategies, which are specifically designed for business people out there. This is important, because the acceleration of technology moves very fast, causing changes in consumer behavior in choosing and buying and selling transactions. This situation encourages business owners to be able to improve and innovate, not only to survive, but also to be able to enjoy the financial benefits of today's technological changes. To prove the effectiveness of digital marketing media in the form of markets, research subjects are needed, namely small business actors who are directly involved with online marketing, interview approaches and their level of success in using digital media (markets). Through this research, it is hoped that small businesses can choose wisely and effectively use digital media (Marketplace) in their marketing activities so that their sales turnover can increase. This research takes the location or object of research in the city of Medan, to be precise at an online shop called TwoHershop. Given that there is intense competition in trade competition in the city of Medan, the authors conducted research in the form of direct interviews with sources who are online store owners to get maximum results.